“Social Media as Multipliers in Nation Branding provided it has a Well Defined Strategy” - Santillán-Vásquez, Manuel (2016)
Villafañe has conducted the first study of Spain’s Country Brand from the Theory of Reputation perspective. According to the author branding is the promise that a company or a country makes to its stakeholders. Villafañe proposes a scientific and professional approach on building a Country Brand and seeks to identify thoroughly the branding promise to then compare it with the identity of a nation. The study delves into the proposition of value and links it to the expectations and interests of diverse stakeholders. This interview intends to assess carefully some key aspects of its methodology.